2018
DOI: 10.3389/fimmu.2018.00726
|View full text |Cite
|
Sign up to set email alerts
|

RIP2 Is a Critical Regulator for NLRs Signaling and MHC Antigen Presentation but Not for MAPK and PI3K/Akt Pathways

Abstract: RIP2 is an adaptor protein which is essential for the activation of NF-κB and NOD1- and NOD2-dependent signaling. Although NOD-RIP2 axis conservatively existed in the teleost, the function of RIP2 was only reported in zebrafish, goldfish, and rainbow trout in vitro. Very little is known about the role and mechanisms of piscine NOD-RIP2 axis in vivo. Our previous study showed the protective role of zebrafish NOD1 in larval survival through CD44a-mediated activation of PI3K-Akt signaling. In this study, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 60 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…S2). Both genes have NOD-like receptor (NLR) domains that possess NACHT (NTPase) and leucine-rich repeat (LRR) protein domains, important for innate immune system antigen interactions [36]. To validate the RNA-seq dataset, quantitative real-time PCR (qRT-PCR) was performed on mineralised tissue growth and degradation markers and showed concordant data between RNA-seq and qRT-PCR assays of all selected amplicons (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…S2). Both genes have NOD-like receptor (NLR) domains that possess NACHT (NTPase) and leucine-rich repeat (LRR) protein domains, important for innate immune system antigen interactions [36]. To validate the RNA-seq dataset, quantitative real-time PCR (qRT-PCR) was performed on mineralised tissue growth and degradation markers and showed concordant data between RNA-seq and qRT-PCR assays of all selected amplicons (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…NOD1 is the best-characterized antibacterial pattern recognition receptor (PRR). Our previous studies have revealed that both NOD1 and its adapter protein RIPK2 influence the expression of CD44a enormously, but not for CD44c 19 21 . Furthermore, NOD1 plays a protective role in larval survival through CD44a-mediated PI3K-Akt signaling 20 .…”
Section: Resultsmentioning
confidence: 96%
“…These findings were also supported by other studies in NOD mice, demonstrating that NOD2-deficient NOD mice were protected from type 1 diabetes development, and this was dependent on the gut microbiota composition ( 127 ), whereas RIP2-deficient NOD mice were not protected ( 120 ). Interestingly, both NOD1 and NOD2 appear to have RIP2 independent functions; NOD2 binds CARD9 to mediate downstream signaling independent of RIP2 ( 128 ), while NOD1 regulates MAPK signaling independent of RIP2 ( 129 ). It is still unclear what the role, if any, NOD1 has in the immunopathogenesis of autoimmune Type 1 diabetes.…”
Section: Inflammasome Priming Is Linked To Type 1 Diabetes Susceptibilitymentioning
confidence: 99%